The effect of the starting material on the thermal decomposition of iron oxyhydroxides - Oliveira, Alcineia C. (2003)
The effect of the iron precursor on the thermal decomposition of iron oxyhydroxides was studied by DSC, DTA and TG in this work. Samples were prepared from iron nitrate, iron sulfate and iron chloride and the thermal curves obtained were analyzed by specific area measurements, X-ray diffraction and Mössbauer spectroscopy. It was found that the iron oxyhydroxide precursors affect the temperatures of the hematite formation as well as the textural properties of the final hematite producing particles with different diameters as following: iron sulfate (3.3 nm)<<iron nitrate (15 nm)<iron chloride (24 nm).